1969
DOI: 10.1088/0022-3727/2/11/307
|View full text |Cite
|
Sign up to set email alerts
|

Charge generation on dielectric surfaces

Abstract: Measurements have been made of the charge density produced on dielectric surfaces by contact with metals of known difference in work function in vacuo. The injected charge density is dependent on the metal work function and, therefore, described by electron transfer for all the materials examined. Values of work function are presented for PVC, 4.85 ev; polyimide, 4.36 ev; PTFE, 4.26 ev; polycarbonate, 4.26 ev; PET, 4.25 ev; polystyrene, 4.22 ev; and nylon 66, 4.08 ev. The positions of some of these materials i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
212
0
1

Year Published

1999
1999
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(220 citation statements)
references
References 5 publications
7
212
0
1
Order By: Relevance
“…The data in Tables III and IV show that the repetition rate is both field and temperature dependent, which would be consistent with a number of interface processes. The lack of detailed knowledge of the interface 28,[41][42][43][44] however, makes it impossible to make an analytical calculation of surface charge replenishment via transfer of charge to surface states, either from the electrode or by ionisation of impurity molecules located in the surface region.…”
Section: Discussionmentioning
confidence: 99%
“…The data in Tables III and IV show that the repetition rate is both field and temperature dependent, which would be consistent with a number of interface processes. The lack of detailed knowledge of the interface 28,[41][42][43][44] however, makes it impossible to make an analytical calculation of surface charge replenishment via transfer of charge to surface states, either from the electrode or by ionisation of impurity molecules located in the surface region.…”
Section: Discussionmentioning
confidence: 99%
“…Specific electron transfer models have been developed for electrification in metalinsulator contact, for example; involving an effective potential difference (Davies 1969) or performing quantum chemical (electron state) calculations (Shirakawa et al 2008). Other models have also studied multiple surface impacts; one involved a capacitance charging model including charge relaxation (electrical discharge) (Matsusyama and Yamamoto 2006).…”
Section: Models and Theories For Dust And Sand Electrificationmentioning
confidence: 99%
“…Other reports have demonstrated that charging can take place in vacuum between freshly cleaved polymer surfaces that were never exposed to the atmosphere. 28,[46][47][48] However, this evidence does not preclude the hydroxide ion mechanism when water is present. It is becoming a recurrent theme in reports that more than one mechanism may be involved in any contact charging event.…”
Section: The Case For Ion Exchangementioning
confidence: 87%
“…A clear distinction needs to be made between metalinsulator and insulator-insulator contacts, these being totally different situations from the point of view of triboelectric charging mechanisms. For metal-insulator contacts, linear relationships were found between charge density of polymer charging and metal work functions [28][29][30] and this was presented as evidence for an electron exchange mechanism. However, it was later reported 31 that this is not always the case.…”
Section: The Case For Electron Exchangementioning
confidence: 99%